Building information modeling integrated with electronic commerce material procurement and supplier performance management system - Ren, Yali; Skibniewski, Mirosław J.; Jiang, Shaohua (Journal of Civil Engineering and Management, 2012)
This paper describes an innovative approach to the integration of Building Information Modeling (BIM) and electronic commerce (e-commerce) in a material procurement process for improved design-construction integration. The paper includes the present applications, benefits, limitations and barriers to e-commerce and BIM in material procurement processes, compares the present commercial BIM based and non-BIM based quantity takeoff and cost estimating software, and identifies potential benefits of integrating BIM and e-commerce software solutions for construction quantity takeoff, cost estimating and procurement processes. The authors propose a framework for integrating BIM for quantity takeoff and cost estimating applications with e-commerce solutions for material procurement and supplier performance evaluation. The paper presents a proposed solution to link BIM-derived data with RS Means unit price cost data to generate accurate cost estimating reports, one weight coefficient-based model to evaluate the performance of material suppliers, and a preliminary version of corresponding BIM-based application integrated with e-commerce software system.